2021
DOI: 10.3390/cancers13194870
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Late Effects and Related Risk Factors in Adolescent and Young Adult Cancer Survivors: A Scoping Review

Abstract: Risk factors associated with late effects in survivors of adolescent and young adult (AYA) cancer are poorly understood. We conducted a systematic scoping review to identify cohort studies published in English from 2010–2020 that included: (1) cancer survivors who were AYAs (age 15–39 years) at diagnosis and (2) outcomes of subsequent malignant neoplasms (SMNs), chronic conditions, and/or late mortality (>5 years postdiagnosis). There were 652 abstracts identified and, ultimately, 106 unique studies were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 143 publications
1
17
0
Order By: Relevance
“…The COVID-19 pandemic had adverse impacts on healthcare utilization among survivors of AYA cancer, for whom healthcare is necessary to manage chronic conditions and prevent second neoplasms [ 9 , 10 ]. We found that survivors of AYA cancers with high financial burdens had nearly threefold increases in their odds of delaying or skipping healthcare appointments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic had adverse impacts on healthcare utilization among survivors of AYA cancer, for whom healthcare is necessary to manage chronic conditions and prevent second neoplasms [ 9 , 10 ]. We found that survivors of AYA cancers with high financial burdens had nearly threefold increases in their odds of delaying or skipping healthcare appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of adolescent and young adult cancers, who were diagnosed between the ages 15 and 39 years (AYA survivors), already had financial and insurance-related barriers to utilizing healthcare before the pandemic [ 8 ]. COVID-19-related health care challenges may cause additional barriers for AYA survivors, affecting their treatment, management of late effects, and screening for second cancers [ 9 , 10 ]. Pandemic-related delays in cancer care have been reported in 40% to 60% of surveyed AYA survivors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, navigators trained in the fear of cancer recurrence [ 10 ], mental health issues in survivorship including post-traumatic stress disorder [ 11 ], as well as occupational therapists with expertise on return to work [ 12 ] need to be employed at a national level. One of the main issues is that late effects of survivors of young adult cancers are not routinely collected [ 13 ], which places an even stronger need for open discussion about the long-term risks from trained professionals and/or navigators. Organizations such as the American Society of Clinical Oncology and the National Comprehensive Cancer Network (NCCN) have established professional guidelines to address issues related to the late-treatments effects for AYA diagnosed with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, in the UK, their treatment and ongoing care falls under specific remits and specialised services until they reach the age of 25 [ 45 ]. The TYA population have also been widely investigated in relation to their experiences of, and issues surrounding, SC and long-term follow-up [ 46 48 ]. Therefore, TYA patients have been excluded from the current review to focus on the adult and elderly population.…”
Section: Methodsmentioning
confidence: 99%